Virtual and augmented reality technologies in Human Performance: a review - Tânia Brusque Crocetta; Sandra Rogéria de Oliveira; Carla Maria de Liz; Alexandro Andrade
Abstract Introduction : Today's society is influenced by Information and Communication Technologies. Toys that were once built by hand have been reinterpreted and have become highly commercialized products. In this context, games using Augmented Reality (AR) and Virtual Reality (VR) technologies are present in the everyday lives of children, youth and adults. Objective : To investigate how Physical Education professionals in Brazil have been making use of AR and VR games to benefit their work. Materials and methods : We only included studies that addressed exercise or physical activity using AR or VR games. We searched the databases of Virtual Health Library (VHL) and Scientific Electronic Library Online (SciELO), using the words augmented reality, virtual reality, exergames, Wii and serious games. Results : Nineteen articles were included in the systematic review. The most frequently used device was the Nintendo(r) Wii, with over 25 different kinds of games. With regard to the subjects of the studies, four studies were conducted with healthy individuals (mean = 65.7), three with patients with Parkinson's disease (mean = 18.0), three with elderly women (mean = 7.7) and two with patients with stroke injury (mean = 6.0). Conclusion : Many physical therapists and occupational therapists use serious games with AR or VR technologies as another work tool, especially for rehabilitation practices. The fact that these technologies are also used in Physical Education classes in Brazil indicates that electronic games are available and can be a tool that can contribute to the widespread adoption of exercise as an enjoyable form of recreation.